HOW TECHNOLOGY AFFECTING RESEARCHERS IN THE ERA OF GENERATIVE AI - Yato, Dhimas Buing Rindi Widra; Zogara, Lukas Umbu; Suharmat, Asep (Universitas Utpadaka Swastika, 2025)
In the rapidly evolving research landscape, generative AI is emerging as a transformative force. This study explores the multifaceted impacts of generative AI on researchers across various disciplines. By automating routine tasks, enhancing data analysis, and generating novel hypotheses, AI tools are significantly boosting productivity and opening new avenues for innovation. However, these advancements also present challenges, including ethical considerations, the need for transparency, and the potential for bias in AI-generated results. Moreover, the integration of AI into research demands the development of new skill sets, presenting both opportunities and risks for researchers. Drawing on recent studies, this article provides a comprehensive overview of how generative AI is reshaping the research landscape and highlights the critical dynamics researchers must navigate in this new era.